1997
DOI: 10.1097/00042560-199702010-00010
|View full text |Cite
|
Sign up to set email alerts
|

HIV and Reproductive Tract Infections in a Total Village Population in Rural Kilimanjaro, Tanzania

Abstract: The aim of this study was to determine the prevalence of HIV infection, other sexually transmitted diseases (STDs), and biological risk factors associated with HIV infection in a rural population in Tanzania. A population-based study of a village population was carried out from July 1991 through January 1992. A total of 3,239 people (83.7%) participated in an HIV serosurvey. The total HIV prevalence was 0.7 and 1.9% among males and females, respectively (odds ratio, OR = 2.5; 95% confidence interval, CI: 1.2-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
40
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 16 publications
9
40
3
Order By: Relevance
“…The prevalence of T. vaginalis was 10.7% in women and 6.3% in men, indicating that it was the most prevalent nonviral STI and a major public health problem in this population. Other community-based studies conducted in Tanzania have estimated T. vaginalis prevalence at greater than 20% among women 12,13 and 11% in men. 14 Vol.…”
Section: Discussionmentioning
confidence: 96%
“…The prevalence of T. vaginalis was 10.7% in women and 6.3% in men, indicating that it was the most prevalent nonviral STI and a major public health problem in this population. Other community-based studies conducted in Tanzania have estimated T. vaginalis prevalence at greater than 20% among women 12,13 and 11% in men. 14 Vol.…”
Section: Discussionmentioning
confidence: 96%
“…We do not have information about the HIV prevalence in the study sites; however, a study in a rural area in the same district found an HIV prevalence of 4.8% in women aged 15-44 years [12]. Since cervical epithelium is thought to be the likely virus entry point [13], the impairment of the physical barrier of the cervical epithelium due to epithelial swelling and disrupted epithelium seen in the FGS cases might enable the entry or exit of HIV.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization has estimated that this infection accounts for almost half of all curable infections worldwide (17). Various studies of African populations have reported the prevalence of vaginal trichomoniasis to be between 11 and 25% (53,57,61). Laga et al reported an incidence of 38% during a 4-month exposure interval among HIV-infected women in Zaire (57).…”
Section: Epidemiologymentioning
confidence: 99%